PEDAGOGICAL-PSYCHOLOGICAL CHARACTERISTICS OF DEVELOPING PROFESSIONAL IDENTITY IN STUDENTS (Universal International Scientific Journal, 2026)
This article discusses the pedagogical and psychological characteristics of the development of professional identity in students. It also describes the special importance of the development of professional identity for representatives of the creative profession, such as future music teachers.
Keywords: professional identity, professional skills, innovative activity, professional skills, musical activity, musical culture, professional motivation, musical culture, socio-cultural environment.